2020
DOI: 10.3390/min10040346
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Reproducible Synthesis of Pure Monohydrocalcite with Low Mg Content

Abstract: Monohydrocalcite (MHC) is a metastable hydrous calcium carbonate that requires Mg in the mother solution during formation in the laboratory. MHC prepared by previously reported methods always contains a large amount of Mg (Mg/Ca ratio up to 0.4) because of the simultaneous formation of amorphous Mg carbonate during synthesis, which has hindered detailed elucidation of the mineralogical characteristics of MHC. Here, we synthesized MHC at low temperature (5 °C) and found that it contained little Mg (Mg/Ca ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Comparison of the PXRD results of synthesis provided at different temperatures but at the same Mg/Ca ratio and pH (9 and 35; 18 and 38; Table 2) showed, MHC at low temperature becomes more stable than aragonite. This observation in consistency with Kitajima et al (2020), who showed preferable MHC formation at low temperature. Moreover, we can suggest that relative abundance of MHC in Ikka Fjord (e.g., Dahl andBuchardt 2006) andcaves (e.g., Onac 2001) is also due to the low temperature during its formation.…”
Section: Monohydrocalcite Formation Conditionssupporting
confidence: 92%
See 2 more Smart Citations
“…Comparison of the PXRD results of synthesis provided at different temperatures but at the same Mg/Ca ratio and pH (9 and 35; 18 and 38; Table 2) showed, MHC at low temperature becomes more stable than aragonite. This observation in consistency with Kitajima et al (2020), who showed preferable MHC formation at low temperature. Moreover, we can suggest that relative abundance of MHC in Ikka Fjord (e.g., Dahl andBuchardt 2006) andcaves (e.g., Onac 2001) is also due to the low temperature during its formation.…”
Section: Monohydrocalcite Formation Conditionssupporting
confidence: 92%
“…Recent studies (Kitajima et al 2020) based on MHC XANES spectra confirmed that Mg could be structurally incorporated in MHC (Mg/Ca ratio up to 0.4). It was also shown, that MHC synthesized at low temperature (5 ˚C) contains little Mg (Mg/Ca ratio < 0.01) and almost no AMC (Kitajima et al 2020). In contrast, Nishiyama et al (2013) assumed that any Mg content measured in MHC can be due to discrete Mg carbonate phase.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The precipitates in the biomimetic experiments were also analyzed by SEM at the same conditions. To compare the difference between biotic and chemically synthesized monohydrocalcite (MHC), the MHC was also synthesized in inorganic solution (initial concentrations: 0.03 mol⋅L –1 MgCl 2 , 0.01 mol⋅L –1 CaCl 2 , 0.015 mol mol⋅L –1 Na 2 CO 3 ) according to the published method ( Kitajima et al, 2020 ). Thus, the formation hydrochemical conditions of chemically synthesized MHC were similar to those of the biotic MHC.…”
Section: Methodsmentioning
confidence: 99%
“…Fukushi et al [34] estimated the solid solubility limit of Mg in the MHC of Mg/Ca = 0.06. Recently, Kitajima et al [35] showed that the structural incorporated Mg in MHC can only be detected from the MHC with very low Mg content (Mg/Ca < 0.01), from the X-ray absorption near edge structure analyses. Therefore, the host of Mg in suspension is likely AMC, which cannot be detected by XRD [34][35][36].…”
Section: Mineralogy Of Suspended Mattermentioning
confidence: 99%